Land use and land use change emissions of forest land in Finnish provinces - an LCA dataset - Lehtilä, Anniina; Ghani, Hafiz Usman; Liu, Xing; Forssén, Anna; Leinonen, Ilkka (Springer Nature, 2025)
Purpose The land use and land use change (LULUC) emissions and removals are an important part of the carbon footprinting of forest products with the life cycle assessment (LCA). For example, in Finland, forests are an important—though reducing—carbon sink, which is not typically visible in global warming potential (GWP) of forest products. To improve the accuracy of forest LCA, a province-level dataset was combined for specific Finnish provinces following a top-down approach. Methods The dataset of GWPLULUC was created from Finnish forest statistics data from 2015 to 2021. A total of eight provinces from the northern and eastern Finland were included. The carbon pools in the dataset included living biomass (trees), mineral soils and drained organic soils. As a case study, the dataset values were applied for m3 and tonne C of harvested wood biomass of Norwegian Spruce, as well as 1 l of bioethanol production and 1 l of E20 (20% blend of bioethanol with petrol) vehicle use. Results and discussion GWPLULUC values varied between the studied provinces, from net negative to net positive. The variation was mostly attributed to living biomass carbon stock, followed by areas of drained organic soils in different provinces. Overall, GWPLULUC showed an increasing trend in 2015–2021. When GWPLULUC was added to the GWP of harvested wood biomass, it dominated and led to net negative GWPs in half the studied provinces. Yet, if GWPLULUC emissions continue increasing, the currently net negative GWPs may approach zero and even become net positive. The contribution of GWPLULUC was also high for bioethanol production and varied between the studied provinces. Conclusions The created dataset will help improving the accuracy of Finnish forest LCA assessments and will be especially important for comparisons between fossil and bio-based products. The findings of the case studies highlight the importance of using province-level data in forest LCA whenever they are not limited by traceability and data availability.
Keywords: life cycle assessment; GHG emissions; soil carbon; forest land; global warming potential; CO2 removals